A bibliometric study on Marburg virus research with prevention and control strategies - Islam, Md. Aminul; Adeiza, Shuaibu Suleiman; Amin, Mohammad Ruhul; Kaifa, Fatema Hasan; Lorenzo, Jose M.; Bhattacharya, Prosun; Dhama, Kuldeep (Frontiers in Tropical Diseases, 2023)
A highly pathogenic RNA containing zoonotic Marburg virus (MARV) is the etiological agent of Marburg virus disease (MVD) which responsible for hemorrhagic fever. This rare disease with high case fatality rate spread directly from infected patients blood, body fluids or indirectly from contaminated substances (cloth, bed, personal protective equipments or medical equipments) and areas. Although, few vaccines against MARV are in the clinical trial but, till now there is no licensed vaccines. As a result, prevention and control guidelines should be followed strictly to minimize this infection. This bibliometric analysis was conducted to utilize narrative evaluation, emphasizing the significance of quantitative approaches and delineating the most interesting topics for researchers using VOS viewer. Marburg Virus” OR “MARV” AND “Diseases” search criteria were used to search for articles published in the years 1962–2022 in this study. Cooccurrence analysis was applied in this research which further characterized different thematic clusters. From this analysis we found 1688 published articles where publications increased annually with a growth rate of 8.78%. It is also observed that United States published the highest number of publications (714, accounting for 42.29%) while United States Army Medical Research Institute of Infectious Diseases published the most literatures (146 papers). Our study indicated that the top 3 authors of the Marburg virus papers were “FELDMANN, HEINZ” of the National Institute of Allergy and Infectious Diseases, United States, “BECKER, STEPHAN” of the Philipps University of Marburg, Germany and “GEISBERT, THOMAS W” of the University of Texas Medical Branch at Galveston, United States. In this study we furthermore observed that “Journal of Virology “has published the most pertinent literatures, totalling 88 articles, followed by “The Journal of Infectious Diseases”, which published 76 relevant papers, and “Viruses” published 52 related papers. The highest cited papers on Marburg Virus was published in the Nature Medicine in 2005, where total citation and citation/year found 522, 29 respectively.